Scutellospora deformata (Scutellosporaceae), a new species of Gigasporales from the Mediterranean sand dunes of Spain - Guillén, Alberto; Serrano-Tamay, Fernando Javier; Peris, Juan Bautista; Arrillaga, Isabel (Phytotaxa, 2021)
A new species S. deformata, that occurs in six locations of marine sand dunes along the eastern Mediterranean coast of Spain is described and illustrated from spores. In the field, the species occurred in the rhizosphere of Ammophila arenaria (Poaceae), Elymus farctus (Poaceae), Otanthus maritimus (Asteraceae), and Echinophora spinosa (Apiaceae). Morphological characters related with outer, middle and inner wall of the glomerospores as well as phylogenetic analysis (partial SSU, ITS1-5.8S region and the partial LSU nrDNA) support the hypothesis that the fungus is a new species of the Scutellosporaceae.